Jejunal Cavernous Hemangioma Mimicking Malignancy With Increased Activity on 18F-FDG PET/CT. (22nd May 2023) - Huang, Wen-Shan; He, Yang-Lin; Liang, Jie; Su, Yu-Lin; Xu, Jie-Hua
Abstract: A 50-year-old woman underwent 18 F-FDG PET/CT to evaluate possible abdominal malignancy, which was revealed by CT. The images showed a large cystic-solid lesion with peripherally increased FDG activity in the left mid-abdomen. Histopathology of the excised lesion confirmed a jejunal cavernous hemangioma. We reported a rare case of jejunal cavernous hemangioma with FDG accumulation on PET/CT, mimicking malignancy.